THE FUNCTION OF ISM TAFḌĪL IN THE NOVEL RAʾAITU RĀMALLĀH BY MOURID BARGHOUTI - Zaini Nur Afifah; Abdul Malik (CMES (Center of Middle Eastern Studies), 2025)
he novel Ra’aitu Rāmallāh depicts the struggle of a young Palestinian man who experienced prolonged exile imposed by Israeli forces until his eventual return to his hometown, Rāmallāh. Within the context of a narrative replete with comparisons between life in exile and life in the homeland, this study adopts a mixed-methods approach to describe both the various forms of ism tafḑ̣īl and their functions in the novel Ra’aitu Rāmallāh by Mourid Barghouti, supported by quantitative data in the form of percentages. The primary source for this research is the Arabic version of the novel, which consists of nine chapters. Based on the theoretical framework of Al-Gulāyainī (1994), 90 instances of ism tafḑ̣īl were identified and categorized into four structural forms: without alif lām and not in the iḑ̣āfah construction (48 items), with alif lām (6 items), in the iḑ̣āfah construction with an indefinite noun (26 items), and in the iḑ̣āfah construction with a definite noun (10 items). Furthermore, the functions of ism tafḑ̣īl were found to fall into four categories: comparative (44 items), superlative (46 items), functioning as an adjective (na‘t) (4 items), and as a predicate (25 items). This research contributes to the understanding of ism tafḑ̣īl by offering insights into its definition, structural variations, and functional roles within the novel.